1990
DOI: 10.1002/art.1780330912
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage proteoglycan‐induced arthritis in BALB/c mice. Antibodies that recognize human and mouse cartilage proteoglycan and can cause depletion of cartilage proteoglycan with little or no synovitis

Abstract: Human fetal cartilage proteoglycan (PG) induces the development of an erosive polyarthritis and spondylitis in BALBIc mice. We have examined the properties of 3 monoclonal antibodies (MAb) to human fetal cartilage PG isolated from immunized mice that cross-react with mouse cartilage PG. Compared with sera from arthritic mice, which contain antibodies reactive with keratan sulfate, MAb 202 (IgG1) reacted only with a protein-related epitope that is distributed on both hyaluronic acid-binding and chondroitin sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…CARTILAGE MATRIX Numerous components of cartilage matrix, such as collagen type II, IX, and XI (Bujia et al, 1994a;Paroczai and Nemeth-Csoka, 1988;Takagi and Jasin, 1992), core protein of proteoglycans (Dayer et al, 1990;Glant et al, 1998;Goodstone et al, 1996), or link proteins (Doran et al, 1995) have antigenic properties and could be involved in transplant rejection. Thus, anti-type II collagen antibodies present in sera of patients with rheumatoid arthritis reacted with chondrocyte membrane antigens (Takagi and Jasin, 1992).…”
Section: Antigens Present Inmentioning
confidence: 99%
“…CARTILAGE MATRIX Numerous components of cartilage matrix, such as collagen type II, IX, and XI (Bujia et al, 1994a;Paroczai and Nemeth-Csoka, 1988;Takagi and Jasin, 1992), core protein of proteoglycans (Dayer et al, 1990;Glant et al, 1998;Goodstone et al, 1996), or link proteins (Doran et al, 1995) have antigenic properties and could be involved in transplant rejection. Thus, anti-type II collagen antibodies present in sera of patients with rheumatoid arthritis reacted with chondrocyte membrane antigens (Takagi and Jasin, 1992).…”
Section: Antigens Present Inmentioning
confidence: 99%
“…This arthritis and spondylitis appear t o be strain specific (but not haplotype specific) and sex related (9). The development of this arthritis is associated with the natural presence of cellular immunity t o mouse PG ( (9), and some are capable of eliciting a loss of PG from articular cartilage in vivo (25). In the present study, we demonstrated that arthritis with spondylitis can be adoptively transferred t o healthy but irradiated mice by a combination of T and B lymphocytes from mice with arthritis.…”
Section: Proteoglycan-induced Polyarthritis and Spondylitis Adoptivelmentioning
confidence: 99%
“…The PG-induced arthritis, described recently, shows many deliveries was approximately the same as the ratio of caesarian similarities to human RA [1][2][3]6,16], and this is the only sections (20%) due to joint alterations of the pelvis in juvenile inflammatory autoimmune animal model which has close to RA [19]. However, most of the pregnancies of arthritic mice 100% incidence in genetically susceptible BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%
“…fetal or newborn human, fetal pig and chondrocytes [6] and able to deplete PGs in articular cartilage canine articular cartilage) PGs [1,2,5]. Remissions and exacer- [3], significantly reduces the onset time of passively transferred bations of local inflammatory processes alternate, leading to the arthritis [6]. Transfer of arthritis, however, never occurs after complete deterioration of articular cartilage and intervertebral injection of serum alone from arthritic animals [6] or after discs as well as to deformities and ankylosis of axial and injecting animals with autoreactive MoAbs to mouse cartilage peripheral joints within a 6-9 month period of the disease [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation